A “Strange Topography of Edges”: Saying Goodbye in Godard and Antonioni - Campbell, Timothy (Aesthetica Preprint, 2023)
In much of the film criticism dedicated to Michelangelo Antonioni, endings loom large. From L’avventura to L’eclisse to Blow Up, critics have focused on how Antonioni’s films end and what lessons an audience ought to draw from them. Often, they emphasize the existential, the ironic, or more simply the poignant. This essay takes a different tack in its examination of the ending of a later film of Antonioni’s, The Passenger, finding in its ending hints about the nature of dispossession. It argues that the film pushes forward a perspective on cinema in which cinema itself becomes an invitation to exit into openness. Through a comparison with Jean-Luc Godard’s 2014 Adieu au langage in which the post-linguistic image is shot through with pathos about what comes after the human, the essay finds in The Passenger a response to Godard’s dire symptomology of the contemporary world mesmerized by its digital devices. It does so by employing the notions of interregnum as well as what Jacques Derrida in a different context refers to as “the apparatus of edges” in order to see where borders and boundaries become visible. In the transformation of lines into edges, borders can be trespassed. The essay concludes with a reflection on the cinematic interregnum more broadly and the need to consider movement and birth together as forming what Jean-Luc Nancy refers to as “an open totality.”